Infrared radiation drying of Moringa oleifera grains for use in water treatment - Vânia R. G. Nascimento; João D. Biagi; Rafael A. de Oliveira; Camila C. Arantes; Luiz A. Rossi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT This study aimed to evaluate the effects of using infrared radiation in the hot-air drying of Moringa oleifera grains on the inner dryer and grain temperatures, energy consumption, and grain quality. An experiment was conducted in a factorial scheme in 2013 to identify the optimum values of the air temperature (30 to 58 ºC) and infrared radiation application time (2.0 to 4.8 min) on moisture content, drying time, drying rate, inner dryer air temperature, grain temperature, energy consumption and quality of grains used as a natural coagulant for water treatment. The results obtained were moisture content from 4.40 to 4.76% wet basis; drying time from 0.50 to 2.00 h; drying rates from 0.70 × 10-3 to 2.05 × 10-3 kgwater kg-1 dry matter min-1; inner dryer air temperatures from 42.24 to 61.82 ºC; grain temperatures from 56.32 to 76.19 ºC; energy consumptions of the fan from 0.05 to 0.20 kWh, electrical resistances from 1.41 to 4.49 kWh; resistances of the infrared heaters from 0.48 to 1.56 kWh; water turbidities from 1.36 to 5.76 NTU; grain protein contents from 34.93 to 37.93%; and peroxide value of grains from 0.009 to 0.052 meq kg-1. Both evaluated factors increased the inner dryer air temperature and grain temperature. The electrical resistances contributed the most to the energy consumption. However, the infrared radiation reduced this consumption. The drying performed with air temperature of 44 °C and infrared radiation time of 3.4 min resulted in the highest protein concentration in the Moringa oleifera L. grains and in greater removal of the water turbidity in the water treatment.